The effect of steam pasteurisation and gamma-irradiation on the microbial profile of Aspalathus linearis (Rooibos) tea and the investigation of the native lactic acid bacteria profile - Groenewald, Jadri (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScFoodSc)--Stellenbosch University, 2023.